2007
DOI: 10.1051/0004-6361:20077197
|View full text |Cite
|
Sign up to set email alerts
|

A massive protostellar core with an infalling envelope

Abstract: Context. Due to the short timescales involved and observational difficulties, our knowledge of the earliest phases of massive star formation remains incomplete. Aims. We aim to explore the physical conditions during the initial phases of high-mass star formation and to detect a genuine massive (mass M > 8 M ) protostar at an early evolutionary stage. Methods. We have launched a multi-wavelength study of young and massive star-forming regions that were identified by the ISOPHOT Serendipity Survey (ISOSS) perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Towards SMM1 East, a Class II-like YSO of intermediate central mass has been identified among several 24 μm sources (Hennemann et al 2008). Birkmann et al (2007) identified two cores in this region with ∼200 M each (at 19.5 K and 17.3 K). HCO + kinematics indicate in-falling gas in both cores.…”
Section: Isossj20298+3559mentioning
confidence: 99%
See 1 more Smart Citation
“…Towards SMM1 East, a Class II-like YSO of intermediate central mass has been identified among several 24 μm sources (Hennemann et al 2008). Birkmann et al (2007) identified two cores in this region with ∼200 M each (at 19.5 K and 17.3 K). HCO + kinematics indicate in-falling gas in both cores.…”
Section: Isossj20298+3559mentioning
confidence: 99%
“…Using the 170 μm ISOPHOT ) Serendipity Survey (ISOSS Bogun et al 1996), we selected 16 candidates for massive (M > 100 M ), cold (T dust < 18 K) objects based on preliminary studies (Krause et al 2003(Krause et al , 2004Birkmann et al 2007). For these sources, the naming convention derives from the FK5 (J2000) coordinates, r for right ascension and d for declination, represented as ISOSSJrrrrr±dddd.…”
Section: Appendix A: Individual Target Descriptionsmentioning
confidence: 99%
“…It presumably stems from warmer dust components or transiently heated very small grains (cf. Birkmann et al 2007;Rawlings et al 2005). The spectral slopes (d log(λF λ )/d log λ) vary in the range 0.3−2.0 for 70 μm < λ < 94 μm.…”
Section: Far-infrared Spectral Slopesmentioning
confidence: 99%
“…Only a relatively small number of candidate sources have been investigated in detail (recently e.g. Beuther & Steinacker 2007;Rathborne et al 2007;Birkmann et al 2007), but results of larger-scale studies also suggest that the lifetimes of massive prestellar cores are very short (Motte et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Core JCMT 18354−0649S has no counterpart in the radio continuum. Multiple lines toward this core including HCN (3-2), H 13 CO + (3-2), and C 17 O (2-1) reveal the typical "blue profile" (Wu et al 2005), indicating that the core is undergoing gravitational collapse (Keto et al 1988;Zhou et al 1993;Zhang et al 1998;Wu & Evans 2003;Wu et al 2005Wu et al , 2007Fuller et al 2005;Wyrowski 2006;Birkmann et al 2007; Klaassen & Wilson 2007;Sun & Gao 2008;Velusamy et al 4 Current address: I. Physikal. Institut, Universität zu Köln, Zülpicher St. 77, D-50937 Köln, Germany.…”
Section: Introductionmentioning
confidence: 99%